ANALISIS PENINGKATAN KOMPETENSI PEDAGOGIK GURU DALAM MENGIMPLEMENTASIKAN DEEP LEARNING DI SEKOLAH - Cut Latifah; Mardiati; Sarianto Thoga Torop; Santi Oktafenti; Muhammad Sopingi; Ri Fazqi Marchi; Anngi Sapana; Jamilah Rambe (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
The quality of mathematics learning is strongly influenced by teachers’ pedagogical competence, particularly in implementing a deep learning approach that emphasizes conceptual understanding, critical thinking, and meaningful learning processes. However, in practice, many teachers still apply procedural and memorization-oriented instruction, resulting in suboptimal implementation of deep learning. This study aims to analyze the improvement of teachers’ pedagogical competence in implementing deep learning in schools, specifically in mathematics instruction. This research employed a quantitative approach with a quasi-experimental design. The subjects of the study were mathematics teachers at the secondary school level, divided into an experimental group and a control group. Data were collected through pedagogical competence questionnaires, classroom observation sheets, and documentation of instructional planning. Data analysis was conducted using descriptive and inferential statistical techniques to examine differences in teachers’ pedagogical competence before and after the intervention. The results indicate a significant improvement in teachers’ pedagogical competence, particularly in lesson planning, implementation of meaningful learning, and evaluation practices aligned with deep learning principles. These findings suggest that systematic implementation of deep learning can effectively enhance the pedagogical competence of mathematics teachers. This study is expected to contribute to teacher professional development and the improvement of mathematics learning practices oriented toward deep conceptual understanding and meaningful learning.